Stereotypes and false consensus: how financial professionals predict risk preferences - Roth, Benjamin; Voskort, Andrea (Journal of economic behavior & organization, 2014)
We analyze the prediction of risk preferences of others using an artefactual field experiment with financial professionals and students. For their prediction, the subjects receive information on multiple demographic characteristics and a self-assessment of risk taking of the target. When analyzing the predictions we find three significant effects: subjects use the demographic information for stereotyping as well as the target's self-assessment on risk taking, and we find a considerable false consensus effect. The false consensus effect is the strongest for experienced professionals. Regarding the prediction's accuracy, we find that the forecasts of the professionals are more accurate than the forecasts of the students.